Ambiguity and logic - Schick, Frederic (Cambridge University Press, 2003)
"In this book, Frederic Schick extends and applies the decision theory he proposed in two previous Cambridge books: Understanding Action (1991) and Making Choices (1997). He shows how the way we see situations affects the choices we make, and he develops a logic of thought responsive to how things are seen. The book considers many questions of choosing and some familiar human predicaments. Why do people in choice experiments act so often against expectations? How might they and the experimenters be looking at different problems in them? Why do people cooperate so often where the textbook logic excludes that? How can there be weakness of will - and must it always be faulted? Does how we see things affect what they mean, and what are people reporting who say that their lives have no meaning for them? These very different questions turn out to have some closely related answers. There are vivid discussions here of cases drawn from many sources. The book will interest all who study how we choose and act, whether they are philosophers, psychologists, or economists - or any combination." Frederic Schick is Professor of Philosophy at Rutgers University.